Advanced exercise physiology essential concepts and applications - Ehrman, Jonathan K. 1962-; Kerrigan, Dennis J. 1974-; Keteyian, Steven J. (Human Kinetics, 2018)
Written by experts in the field, Advanced Exercise Physiology: Essential Concepts and Applications builds upon foundational topics and looks further into key physiological components to help advanced students gain a deeper level of understanding.